Identification of Structural Elements Towards Disasters: A Case Study of Osing Architecture - Wijaya, Elvina Shanggrama; Dharmatanna, Stephanus Wirawan; Birawa, Emmanuel Nicholas (Institut Teknologi dan Bisnis Ahmad Dahlan, 2025)
Indonesia is an archipelagic country consisting of various tribes and cultures, one of which is the Osing Tribe in Banyuwangi, located at the eastern tip of Java Island, near Bali Island. The culture of the Osing tribe is manifested in the traditional Osing house architecture, especially in Kemiren Village, which is built from a combination of Osing's unique technology and art. From its position, the Banyuwangi area is located at the boundary of tectonic plates, which results in the potential for natural disasters such as volcanic eruptions, earthquakes, landslides, and tsunamis. This research aims to study the structural design of the traditional Osing tribe house in responding to these disasters threat. The identification of the structural elements is then analyzed to determine how the building will transmit the axial and lateral load, as well as withstand disasters. The result is that the Osing tribe house has applied the local wisdom, manifested in the house’s tectonic design. The details of the building could respond and distribute the loads caused by disaster. Responding to the load from the volcanic ash, the Osing house’s roof needs reinforcement to sustain its rigidity.